Effects of Tuberculosis, Race, and Human Gene SLCO1B1 Polymorphisms on Rifampin Concentrations - Weiner, Marc (American Society for Microbiology (ASM), 2010)
Rifampin has concentration-dependent activity against Mycobacterium tuberculosis. However, marked intersubject variation of rifampin concentrations occurs. In this study, we evaluated rifampin pharmacokinetics in relation to tuberculosis, geographic region, race, and single nucleotide polymorphisms of the human transporter genes SLCO1B1, SLCO1B3, and MDR1. Seventy-two adults with pulmonary tuberculosis from Africa, North America, and Spain were evaluated during multidrug intensive-phase therapy, and their results were compared to those from 16 healthy controls from North America. Rifampin pharmacokinetic values were similar between tuberculosis patients and controls (geometric mean [GM] area under the concentration-time curve from 0 to 24 h [AUC(0-24)] of 40.2 versus 40.9 μg·h/ml; P = 0.9). However, in multivariable analyses, the rifampin AUC(0-24) was significantly affected by rifampin dosage (in mg/kg of body weight), polymorphisms in the SLCO1B1 gene, and the presence of tuberculosis by geographic region. The adjusted rifampin AUC(0-24) was lowest in patients with tuberculosis from Africa compared to that in non-African patients or control subjects. The adjusted rifampin AUC(0-24) was also 36% lower among participants with SLCO1B1 genotype c.463CA than that among participants with SLCO1B1 genotype c.463CC (adjusted GM, 29.8 versus 46.7 μg·h/ml; P = 0.001). Polymorphisms in the SLCO1B1 gene associated with lower rifampin exposure were more frequent among black subjects. In conclusion, marked intersubject variation of the rifampin AUC(0-24) values was observed, but the mean values of the AUC(0-24) did not significantly vary between patients with tuberculosis and healthy controls. Lower rifampin exposure was associated with the polymorphism of the SLCO1B1 c.463C>A gene. When adjusted for the patient mg/kg dosage and transporter gene polymorphisms, rifampin exposure was lower in patients with tuberculosis, which suggests that additional absorption or metabolic processes affect rifampin exposure with tuberculosis disease.